A study of morbidities among electronic equipment manufacturing workers in Goa - Mhalshekar, Vishwaraj K.; Kunkolienkar, Rudra Prasad; Naik, Saideep Deepak; Rodrigues, Eli Jonathan; Chauhan, Pradeep Singh; Cacodcar, Jagadish Anil (International Journal Of Community Medicine And Public Health, 2021)
Background: Electronic equipment manufacturing units are among the most common industries all over the world. It involves a large amount of employees required for processing, manufacturing, building and setting up electronic equipments. Workers are usually sedentary and involve very less physical movement. Chronic illnesses are common among these sedentary workers of which most important are cardiovascular diseases, hypertension, obesity and diabetes. Considering the importance of the subject and the lack of published evidence on health status of electronic manufacturing workers, our study was done with an aim of assessing selected morbidities among electronic equipment manufacturing units in Goa. Methods: Our retrospective record based cross-sectional study was conducted over a period of one month in March 2019. The study was done in electronic equipment manufacturing workers. Data included sociodemographic details of the workers and details of periodic medical check-up. The data analysis was done using and analyzed using SPSS version 22. Chi square test was used to assess association between qualitative variables. Results: Among the 109 electronic manufacturing workers, it was observed that 10.1% (11) had obesity with a BMI >30, 24.8% (27) had hypertension (>140/90) and 31.2% (34) had diabetes mellitus with HbA1c >6.5. In addition, 24.8% (27) had far vision defect and 39.4% (43) had near vision defect. 42.2% (46) had abnormal lung function tests, 0.9% (1) had hearing disability and 4.6% (5) had abnormal ECG findings. Among male workers 0.9% (1) had elevated PSA levels, whereas all PAPs smear reports were normal among female workers. Conclusions: This study highlights the need of periodic medical check-up of the electronic manufacturing workers for timely detection and early management of their health problems.